Towards Smallholder Coffee Farmers Empowerment in Manggarai Regency, East Nusa Tenggara Province - Iqbal, Muhammad; Muslim, Chairul (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 11, No. 1 Juli 2011, 2011)
-